"First They Came for the Muslims": Psychoanalytic reflections on the threat and the challenge of contemporary populism. (9th August 2018) - Kemp, Martin
Abstract: This paper is a response to the rise of populism across and beyond the Western world. It takes seriously the possibility that there are parallels between the unconscious dynamics underlying contemporary threats to liberal democracy and those which were mobilised during the inter‐war crisis in Europe. The paper explores how historical contexualization and ideological orientation shape psychoanalytic theorizing, with significant consequences for our conceptualizations of the nature of the "fascist" mind. It suggests that a "basic fault" in the evolution of nation states that seek to reconcile political democracy and economic anarchy provides the conditions in which irrationality and the politics of scapegoating is a permanent temptation. It is this, the paper argues, that provides the link between inter‐war fascism and the present rise of populist movements around the world.